2023
DOI: 10.1038/s41598-023-40096-7
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid as potential immunostimulant in metabolism pathways of hybrid grouper fingerlings (Epinephelus fuscoguttatus × Epinephelus lanceolatus) infected with Vibrio vulnificus

Abstract: Grouper culture has been expanding in Malaysia due to the huge demand locally and globally. However, due to infectious diseases such as vibriosis, the fish mortality rate increased, which has affected the production of grouper. Therefore, this study focuses on the metabolic profiling of surviving infected grouper fed with different formulations of fatty acid diets that acted as immunostimulants for the fish to achieve desirable growth and health performance. After a six-week feeding trial and one-week post-bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…Previous studies have found that Shewanella can protect Litopenaeus vannamei from bacterial infection to improve survival [50]. In our study, Shewanella was found to be significantly enriched in one-month-old juvenile shrimp with enhanced immune-related metabolites such as glycine serine and threonine metabolism [51]. These results were consistent with the relative abundance of Shewanella in Litopenaeus vannamei [49].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found that Shewanella can protect Litopenaeus vannamei from bacterial infection to improve survival [50]. In our study, Shewanella was found to be significantly enriched in one-month-old juvenile shrimp with enhanced immune-related metabolites such as glycine serine and threonine metabolism [51]. These results were consistent with the relative abundance of Shewanella in Litopenaeus vannamei [49].…”
Section: Discussionsupporting
confidence: 90%